Role of Civilizational Populism in Shaping Religious Othering: A Comparative Analysis of India and Pakistan (Journal of Politics and International Studies, 2025)
Civilizational conflicts have dominated debate since Huntington’s “Clash of Civilizations,” which argued that cultural and religious identities would define future wars. With the rise of populism often linked to authoritarian politics, claims of civilizational superiority are increasingly used to dismiss perspectives seen as contrary to dominant cultural narratives. Civilizational populism often divides societies into categories mainly virtuous ‘people’ and perceived ‘enemies.’ In India, its rise is visible in populist rhetoric and radical policies but also in the persistent framing of the state as the product of a broader civilizational project. In Pakistan, civilizational populism has historically been more symbolic, used to foster national integration amid ethnic assertions and demands for provincial autonomy. In both states, however, civilizational hostility is reinforced through societal indoctrination and the securitization of religious ‘others,’ portrayed as less human and unworthy of empathy. This embeds an imagination of the state as an extension of a singular civilization, damaging democratic norms and equal human rights. This research explores India’s shift from national identity to civilizational self-definition & studies how civilizational imaginaries shape populist state identities in India and Pakistan, while exploring why civilizational memories fuel religious othering in both states.